2020
DOI: 10.1101/2020.03.18.20035816
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and utilization of an intelligent application for aiding COVID-19 diagnosis

Abstract: 2 0 2 1 2 2 All rights reserved. No reuse allowed without permission. ABSTRACT 2 5Background: COVID-19 has been spreading globally since emergence, but the 2 6 diagnostic resources are relatively insufficient. 7Results: In order to effectively relieve the resource deficiency of diagnosing 2 8 COVID-19, we developed a machine learning-based diagnosis model on basis of 2 9 laboratory examinations indicators from a total of 620 samples, and subsequently 3 0implemented it as a COVID-19 diagnosis aid APP to facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 8 publications
1
71
0
1
Order By: Relevance
“…8 So far only one study analyzed diagnosis of COVID-19 with routinely-collected data, in this case to predict cases using as controls patients with viral pneumonia by applying logistic regression. 9 Another study of 53 patients from two hospitals in Wenzhou, China, analyzed the accuracy of five machine learning algorithms to predict Acute Respiratory Distress Syndrome (ARDS) in patients with COVID-19. 10 Two other studies applied machine learning algorithms to predict mortality in patients with COVID-19, using patient data from Kaggle and China.…”
Section: Discussionmentioning
confidence: 99%
“…8 So far only one study analyzed diagnosis of COVID-19 with routinely-collected data, in this case to predict cases using as controls patients with viral pneumonia by applying logistic regression. 9 Another study of 53 patients from two hospitals in Wenzhou, China, analyzed the accuracy of five machine learning algorithms to predict Acute Respiratory Distress Syndrome (ARDS) in patients with COVID-19. 10 Two other studies applied machine learning algorithms to predict mortality in patients with COVID-19, using patient data from Kaggle and China.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we reached out to authors to include studies that were not publicly available at the time of the search, 7 8 and included studies that were publicly available but not on the Living Systematic Review 6 list at the time of our search. [9][10][11][12] Databases were initially searched on 13 th March 2020, with an update on 24 th March 2020. All studies were considered, regardless of language or publication status (preprint or peer reviewed articles).…”
Section: Methodsmentioning
confidence: 99%
“…One study developed a model to detect COVID-19 pneumonia in fever clinic patients (estimated C-index 0.94), 10 one to diagnose COVID-19 in suspected cases (estimated C-index 0.97), 30 one to diagnose COVID-19 in suspected and asymptomatic cases (estimated C-index 0.87), 12 one to diagnose COVID-19 using deep learning of genomic sequences (estimated Cindex 0.98), 35 and one to diagnose severe disease in symptomatic paediatric inpatients based on direct bilirubin and alaninetransaminase (reporting an F1 score of 1.00 , indicating 100% observed sensitivity and specificity). 24 Only one study reported assessing calibration, but it was unclear how this was done.…”
Section: Diagnostic Models To Detect Covid-19 Infection In Symptomatimentioning
confidence: 99%
See 1 more Smart Citation
“…In the present manuscript, we describe this population and highlight the differences between patients who actually tested positive to SARS-COV-2 and those who did not. Few attempts in applying arti cial intelligence torapidly predict positivity/negativity to SARS-COV-2 were made since the outbreak, using mostly CT imaging and lab results, collected in Chinese population (42)(43)(44). Nevertheless, we present the rst European attempt and promising results applying arti cial intelligence to rapidly predict positivity/negativity to SARS-COV-2 using only basic clinical data, available in the vast majority of emergency departments all over the world.…”
Section: Discussionmentioning
confidence: 99%